Island of Discord: Tenedos in the Fourteenth-Century Byzantine-Venetian Relations - Kushch, Tatiana Viktorovna (Antičnaâ drevnostʹ i srednie veka, 2022)
This article examines the history of Venice’s struggle for the control over the Byzantine island of Tenedos. In the Late Middle Ages, this island was of great strategic importance, since its owner could control the passage of ships through the Hellespont to the Marmara and the Pontos. Following the fourth Crusade, Venice captured Tenedos, but Byzantium returned the island in 1305. Throughout the fourteenth century, La Serenissima repeatedly attempted to get the cession of the island from the Empire, nevertheless, avoiding military conflict and preferring to solve the “Tenedos question” by diplomacy. In the second half of the fourteenth century, the Venetians, taking the advantage of conflicts within the ruling imperial family, offered financial assistance to one of the parties several times in exchange for the transfer of the island. The fate of Tenedos was also discussed during diplomatic meetings and negotiations. Emperor John V Palaiologos, searching for the alliance with Venice, promised the transfer of the island several times, but never realized it. In result, Venice, using the weakening of the Empire, seized the island in 1376. The capture of Tenedos by the Venetians was disputed by the Genoese and led to a war (1379–1381), in which Byzantium occupied the position of an outside observer. The struggle for Tenedos not only illustrates the peculiarities of political and diplomatic contacts between Byzantium and Venice, but also reflects the changes in the geopolitical situation in the Eastern Mediterranean as the final decline of the Empire and the intensification of the Venetian–Genoese contradictions.